2024
DOI: 10.3390/cancers16030580
|View full text |Cite
|
Sign up to set email alerts
|

G Protein-Coupled Receptors and Ion Channels Involvement in Cisplatin-Induced Peripheral Neuropathy: A Review of Preclinical Studies

Gabriela Becker,
Samuel Felipe Atuati,
Sara Marchesan Oliveira

Abstract: Cisplatin is a platinum-based chemotherapy drug widely used to treat various solid tumours. Although it is effective in anti-cancer therapy, many patients develop peripheral neuropathy during and after cisplatin treatment. Peripheral neuropathy results from lesions or diseases in the peripheral somatosensory nervous system and is a significant cause of debilitation and suffering in patients. In recent years, preclinical studies have been conducted to elucidate the mechanisms involved in chemotherapy-induced pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 100 publications
(205 reference statements)
0
1
0
Order By: Relevance
“…A simulation analysis suggested that reductions in the activity of voltage-gated K+ channels (K V ) induced by oxaliplatin and enhancements in sodium channel activity can account for the documented nociceptor hyperexcitability [29,30]. Chemotherapeutics act mainly on the expression and activity of Kv7 and Kv11, which mediate the repolarization and stabilization of the membrane potential in nociceptive neurons, leading to depolarization and increased excitability of these neurons, resulting in increased pain sensitivity and neuropathic pain [31].…”
Section: Neurophysiological Mechanisms Of Cipnmentioning
confidence: 99%
“…A simulation analysis suggested that reductions in the activity of voltage-gated K+ channels (K V ) induced by oxaliplatin and enhancements in sodium channel activity can account for the documented nociceptor hyperexcitability [29,30]. Chemotherapeutics act mainly on the expression and activity of Kv7 and Kv11, which mediate the repolarization and stabilization of the membrane potential in nociceptive neurons, leading to depolarization and increased excitability of these neurons, resulting in increased pain sensitivity and neuropathic pain [31].…”
Section: Neurophysiological Mechanisms Of Cipnmentioning
confidence: 99%